2017
DOI: 10.1161/circoutcomes.116.003202
|View full text |Cite
|
Sign up to set email alerts
|

Syncope and Its Impact on Occupational Accidents and Employment

Abstract: Background— First-time syncopal episodes usually occur in adults of working age, but their impact on occupational safety and employment remains unknown. We examined the associations of syncope with occupational accidents and termination of employment. Methods and Results— Through linkage of Danish population-based registers, we included all residents 18 to 64 years from 2008 to 2012. Among 3 410 148 eligible individuals, 21 729 with a first-time diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…A recent investigation found a 1.4-fold higher risk of work accidents in subjects who suffered from recurrent syncope compared with the employed general population [7]. In addition, work accidents among syncope patients were more frequent in those working in manual labor sectors [7] that are often characterized by high risk.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent investigation found a 1.4-fold higher risk of work accidents in subjects who suffered from recurrent syncope compared with the employed general population [7]. In addition, work accidents among syncope patients were more frequent in those working in manual labor sectors [7] that are often characterized by high risk.…”
Section: Discussionmentioning
confidence: 99%
“…However, its consequences may be serious. Indeed, the sudden loss of postural tone and consequent falls may cause severe damage to the fainter [3,29,30] and third parties when occurring during high risk activities [7,13,14]. In keeping with this hypothesis are the Health and Safety at Work in Europe Reports, suggesting that most of fatal accidents occur as a consequence of actions characterized by “loss of control”, “slipping”, ”stumbling”, and “falling”.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that more than 70% of patients have anxiety or depression and require changes to daily activities such as employment or driving [6]. Syncope doubles the risk of occupational accidents termination of employment [10]. Syncope is also a well-known risk factor for falls and associated injuries; 5% of syncope patients present with a severe injury and trauma in the emergency department [11].…”
mentioning
confidence: 99%